Mysterious Allergy Caused by Tick Bite: Alpha-Gal Syndrome - Muhammed Nalçacı (Türkiye Parazitoloji Dergisi, 2024)
Alpha-Gal syndrome (AGS) manifests as an intricate allergic response characterised by the formation of specific immunoglobulin E (IgE) antibodies targeting a carbohydrate termed galactose-a-1.3-galactose (a-Gal). Alpha-Gal antigens, which play a role in AGS, have been detected in the salivary glands and saliva of various tick species, especially Amblyomma americanum. Identifying these antigens in tick saliva underlines the potential role of tick bites in sensitising individuals to a-Gal and contributes to the complex immunological processes associated with AGS. When people with a-Gal allergy eat beef, pork, lamb, or the flesh of other mammals, they experience an allergic reaction that causes various symptoms, including rash, nausea, vomiting, and diarrhoea. In some cases, AGS can be life-threatening requiring emergency medical attention. Moreover, these reactions do not occur only due to red meat; intake of medical drugs, vaccines, and antidotes containing a-Gal epitopes can also trigger allergies. The fact that the symptoms causing IgE antibodies are directed against a carbohydrate moiety the unusual delay between food consumption and the onset of symptoms, and the differences in the reactions shown by a-Gal allergy make a-Gal syndrome an unprecedented allergic disease and distinguish it from other food allergies. Interestingly, a-Gal antigens involved in the development of AGS have been discovered in salivary secretions of different tick species in several continents. However, the underlying causes of a-Gal-specific IgE production and immune responses to tick bites are not fully understood. This complex system is crucial for identifying and developing new therapies for the disease. This article reviews the evolution of a-Gal, the current understanding of AGS and its relationship to tick species.